Development of webtoon-based electronic comics in history subjects in senior high school - Ardandi, Jefri; Susanti, Retno (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
This research aims to produce valid and effective webtoon-based electronic comic learning media for high school students. This research is a type of development research that uses the ADDIE development model (analysis, design, development, implementation, and evaluation). The data collection techniques used consist of expert validation tests. this validation process assesses aspects such as material, media, and learning design. in addition, individual trials were conducted involving three students and small group trials involving eight students. the last was a field trial involving all students in the class. the data analysis used in this study consisted of expert validation data analysis using validity level categories based on Sugiyono's theory and analysis of student learning outcomes tests obtained from pretest and posttest results and then calculating the analysis of test data using the N-gain criteria.The results of this study indicate that this learning media was assessed by three expert validations consisting of material experts, media experts, and learning design experts. The results of material validation amounted to 4.26 very valid categories, the results of media validation amounted to 4.73 very valid categories, and the results of learning design expert validation amounted to 3.84 valid categories. The effectiveness of using webtoon-based electronic comic learning media can be seen in learning outcomes that have increased by 45% with an N-gain of 0.79 in the high category. Based on the results of the study, it can be seen that this webtoon-based electronic comic learning media is valid and effective and feasible to use. Based on the results of this study, the researchers concluded that the webtoon-based electronic comic learning media developed by researchers is valid and has an effective impact on student learning outcomes. in addition, this webtoon-based electronic comic learning media is suitable for use in classroom learning and also this media is very practical to use both in the classroom and outside the classroom.